Cognitive Conflict-Based E-Book with Real Experiment Video Analysis Integration to Enhance Conceptual Understanding of Motion Kinematics - Mufit, F.; Asrizal, A.; Puspitasari, R.; Annisa N, A. (Jurnal Pendidikan IPA Indonesia, 2022)
Students find it challenging to understand motion concept or mechanics in physics learning and often experience misconceptions. There is also a lack of teaching materials that promote conceptual understanding. This study aims to produce a valid, practical, and effective e-book based on cognitive conflict to enhance conceptual understanding. This research used explanatory sequential mixed methods. The effectiveness test was carried out through an experimental method with a pretest-posttest control group design. Using the cluster random sampling, 61 science students performed as the samples. The research instruments used were interview guides, observation sheets, questionnaires, and two-level multiple-choice concept tests. The data were analyzed qualitatively and quantitatively using Aiken's V formula, the percentage technique, and the Mann-Whitney hypothesis test. This study produced an e-book according to the four syntaxes of the cognitive conflict-based learning model (CCBL). Real experiment video analysis was integrated into the third syntax. The e-book is valid in content, construct, language, and graphics, with an average of 0.83 in the high category. This e-book is practical in terms of user convenience, attractiveness, and benefits, with an average of 79.6 in the strong category. This e-book is effective, with a significant effect of 0.001 0.05 on conceptual understanding and misconceptions. We concluded that the cognitive conflict-based e-book with real experiment video analysis integration is valid, practical, and effective in enhancing students' conceptual understanding of motion kinematics.